Identification of management indicators and their application for the sustainability of shopping centers in Peru - Falconí, Rodolfo Elias (2024)
In Peru, the creation of shopping centers as an alternative to traditional food markets or neighborhood warehouses is becoming increasingly important. Taking into consideration the aforementioned, this work aims to identify and promote the application of management indicators for the sustainability of shopping centers in Peru. For this reason, analysis techniques were applied based on surveys whose emphasis is focused on the attributes of shopping centers, from the perspective of customers and the respective correlation of their dependent variables: traffic and sales. The results show that the difference in marketing strategies significantly influences the positioning of shopping centers.